Problematizing capitalism(s): Big difference? - Peck, Jamie (Environment & Planning A, 2019)
In the article, the author examines the social science theories of Fred Block, particularly on such topics as capitalism, finance, markets, and government. Other topics include Block's opinions on Polanyian socioeconomics, his thoughts on economic diversity and capitalist transformation, as well as the universalist model of capitalism as free-market globalism.
Geography
Keywords: BLOCK; Fred L.; capitalism; finance; free enterprise; markets; social sciences; the state